2008
DOI: 10.1165/rcmb.2007-0323oc
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Caveolin-1 Protects against Oxidative Lung Injury via Up-Regulation of Heme Oxygenase-1

Abstract: Acute lung injury (ALI) is a major cause of morbidity and mortality in critically ill patients. Hyperoxia causes lung injury in animals and humans, and is an established model of ALI. Caveolin-1, a major constituent of caveolae, regulates numerous biological processes, including cell death and proliferation. Here we demonstrate that caveolin-1-null mice (cav-1 2/2 ) were resistant to hyperoxia-induced death and lung injury. Cav-1 2/2 mice sustained reduced lung injury after hyperoxia as determined by protein l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 51 publications
(95 reference statements)
7
58
1
Order By: Relevance
“…Our previous studies demonstrated that deletion of cav-1 protected against hyperoxia-induced cell death (22). Previous studies published by others have established that hyperoxia induces cell death via both necrosis and apoptosis (47).…”
Section: Deletion Of Cav-1 Protected Against Hyperoxia-induced Apoptomentioning
confidence: 84%
See 2 more Smart Citations
“…Our previous studies demonstrated that deletion of cav-1 protected against hyperoxia-induced cell death (22). Previous studies published by others have established that hyperoxia induces cell death via both necrosis and apoptosis (47).…”
Section: Deletion Of Cav-1 Protected Against Hyperoxia-induced Apoptomentioning
confidence: 84%
“…Our group has previously shown that deletion of cav-1 protects against ALI. Deletion of cav-1 protected both hyperoxia-induced lung injury in vivo and hyperoxic cell death in vitro (22). The mechanisms of this protective effect remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Cav-1 in pulmonary diseases remains controversial, and can have protective (23)(24)(25) or deleterious (26,27) functions. Furthermore, the role of Cav-1 in COPD pathogenesis remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…37 Moreover, Cav-1 has been demonstrated in lung epithelial cells to directly interact with Nrf2 to suppress its nuclear translocation, thereby diminishing the induction of ARE-linked antioxidant defense genes 38 ; in addition, it can also interact with HO-1, an Nrf2/ARE-regulated antioxidant enzyme, 39 to attenuate its activity as shown in lung fibroblasts. 40 Taken together, the enhanced Cav-1 expression observed in EC exposed to disturbed FSS 36,41 is likely to contribute to enhanced impaired vascular function, oxidative stress and inflammation, not only via the reduction in NO synthesis but also possibly through diminished cytoprotective activities of both Nrf2 and HO-1.…”
Section: Nrf2 a Mechanosensitive Transcription Factor 21mentioning
confidence: 99%